2022
DOI: 10.1007/s10571-022-01296-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of miR-483-5p Against Cardiac Arrest-Induced Mitochondrial Dysfunction Mediated Through the TNFSF8/AMPK/JNK Signaling Pathway

Abstract: Substantial morbidity and mortality are associated with postcardiac arrest brain injury (PCABI). MicroRNAs(miRNAs) are essential regulators of neuronal metabolism processes and have been shown to contribute to alleviated neurological injury after cardiac arrest. In this study, we identified miRNAs related to the prognosis of patients with neurological dysfunction after cardiopulmonary resuscitation based on data obtained from the Gene Expression Omnibus (GEO) database. Then, we explored the effects of miR-483-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…MiR-4798-3p was indicated to modulate TLR4 and STAT3, and it was closely linked with the prevalence of atrial fibrillation in males and also could regulate genes involved in the pathogenesis of AF [63]. MiR-483-5p was found to be elevated in people with AF, which suggests that it could be used to predict AF [64], and it can exert neuroprotective effects after cardiopulmonary resuscitation by blocking ROS production and reducing MDA activity to attenuate oxidative stress injury [65]. Furthermore, studies have shown that miR-483-5p is associated with coronary plaque rupture and the formation of local thrombi, and its expression is significantly increased in both autoimmune myocarditis and acute myocardial infarction (AMI) [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-4798-3p was indicated to modulate TLR4 and STAT3, and it was closely linked with the prevalence of atrial fibrillation in males and also could regulate genes involved in the pathogenesis of AF [63]. MiR-483-5p was found to be elevated in people with AF, which suggests that it could be used to predict AF [64], and it can exert neuroprotective effects after cardiopulmonary resuscitation by blocking ROS production and reducing MDA activity to attenuate oxidative stress injury [65]. Furthermore, studies have shown that miR-483-5p is associated with coronary plaque rupture and the formation of local thrombi, and its expression is significantly increased in both autoimmune myocarditis and acute myocardial infarction (AMI) [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, miR-483-5p plays a crucial role in protecting against neurological injury induced by cardiac arrest. Specifically, miR-483-5p is significantly downregulated in hippocampal samples from patients with neurological injury after cardiac arrest compared to the normal group [ 61 ] ( Table 1 , Figure 2 ). Brain injury following cardiac arrest is mainly caused by the generation of mitochondrial reactive oxygen species (ROS), which can be inhibited by promoting mitochondrial biogenesis and reducing ROS generation.…”
Section: Role Of Mir-483-5p In Other Human Diseasesmentioning
confidence: 99%
“…MiR-483-5p targets TNFSF8 to achieve this effect and protect against neurological impairment. Overexpression of miR-483-5p reduces protein expression of Bax and cleaved caspase 3, thereby inhibiting cytochrome c release and ROS generation from mitochondria, which alleviates cell injury by ischemia–reperfusion [ 61 ]. The inhibition of miR-483-5p in rats results in more severe hippocampal damage than the control group after cardiac arrest.…”
Section: Role Of Mir-483-5p In Other Human Diseasesmentioning
confidence: 99%